1981
DOI: 10.1103/physreva.23.1745
|View full text |Cite
|
Sign up to set email alerts
|

Energy dependence of alignment in foil collision-excitedn=3states of He i

Abstract: We have measured the beam-foil collision-induced alignment of the 3p 1 P, 3p 3 P, 3d 1 D, and 3d 3 D states of He I for He + beam energies between 30 and 1300 keV. The alignment of all four states is found to vary with beam-current density as well as energy. The number of secondary electrons emitted per incident ion, γ, has also been measured as a function of foil temperature and beam energy between 400 and 1400 keV. The rate of change of both alignment and γ with foil temperature exhibits a general correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1982
1982
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 52 publications
0
7
1
Order By: Relevance
“…It is important to note that the changes in foil structure and in the Balmer-u polarization can be brought on more quickly by irradiating at larger current densities; however, they still occur when one irradiates the foil at lower current densities for a longer period of time. This observation is substantially differe'nt from that of Hight et al [2] and Gay and co-workers [3,4] where they report on normal-incidence alignment measurements of He 1 radiation following transmission of (40-1300)-keV helium ions through a-C foils. They found that the alignment increased with beam-current density and this increase was correlated to an increase in the foil temperature and an associated decrease in the secondary-electron yield.…”
Section: Introductioncontrasting
confidence: 62%
See 1 more Smart Citation
“…It is important to note that the changes in foil structure and in the Balmer-u polarization can be brought on more quickly by irradiating at larger current densities; however, they still occur when one irradiates the foil at lower current densities for a longer period of time. This observation is substantially differe'nt from that of Hight et al [2] and Gay and co-workers [3,4] where they report on normal-incidence alignment measurements of He 1 radiation following transmission of (40-1300)-keV helium ions through a-C foils. They found that the alignment increased with beam-current density and this increase was correlated to an increase in the foil temperature and an associated decrease in the secondary-electron yield.…”
Section: Introductioncontrasting
confidence: 62%
“…The different systems studied and beam energies used in our work compared to the works of Hight et al , [2] Gay and co-workers [3,4], and Winter [5] [2] Gay and co-workers [3,4], and Winter [5] may be attributed to an unknown inhuence from the nickel mesh. However, our very early experiments without a nickel mesh do not suggest this to be the case.…”
Section: Introductionmentioning
confidence: 48%
“…Hight et aI1977, Gay et a1 1981, Andra 1974. This is true for all beam energies, and very little dependence on beam energy is observed (Schectman et al 1980, Gay et al 1981 .…”
Section: Polarized Light From Thin Foil Excitationmentioning
confidence: 54%
“…The dependence on the adopted survival probability may be estimated from the difference introduced by two choices of the parameter dvao: shifting the edge of the bulkelectron density (and thereby the base of the survival probability) by half the distance between the two topmost layers, results only in a moderate modification of the polarization in Fig. However, as long as a quantitative theory is not available and the explanation of general trends is the principal aim, we may rely on an overall similarity of polarization measurements of M/I(cO, S/I(e) for different transitions and beam energies in He [28], and the remarkable similarity of the energy dependence of M/I(c~=O) for Ly~ [29,30] and some He transitions for a carbon target [14] and different foil materials (C, Au, Ag) [31], though the absolute values of the polarizations are shifted by several percent. Beam foil data for the theoretically simplest projectile -the proton -are scarce and unfortunately do not include the Stokes parameters S/I or C/Ithough circular polarization measurements of Ly~ have been accomplished for collisions with gas targets [27].…”
Section: Resultsmentioning
confidence: 99%
“…A number of other models for the production of circular polarization has been proposed: collisions of the projectile with different surface regions [8], capture of localized or delocalized target electrons [9][10][11] and (for grazing incidence only) the scattering from surface plasmons [12]. This mechanism has been favoured in the interpretation of the energy dependence of the alignment [14] by comparing the linear polarization after beam-foil interaction at normal incidence with polarization data from gas targets. excitation, deexcitation, ionization of the projectile [13] have been neglected.…”
Section: Introductionmentioning
confidence: 99%